2006
DOI: 10.1038/modpathol.3800571
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of cytologic findings and chromosomal instability detected by fluorescence in situ hybridization in breast fine-needle aspiration specimens from women at high risk for breast cancer

Abstract: Cytologic evaluation of ductal lavage or random periareolar fine-needle aspiration (FNA) specimens has been proposed to improve risk stratification of women at high risk for breast cancer. However, cytologic assessment of morphologic changes is subjective. To assess the utility of fluorescence in situ hybridization (FISH) in the categorization of breast lesions, we prospectively evaluated 32 random periareolar FNA specimens from 27 women at high risk for breast cancer. Cytologic specimens were prepared using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 19 publications
2
19
0
Order By: Relevance
“…The RPFNA procedure is well tolerated among women participating in breast cancer prevention trials, and the risk of infections requiring oral antibiotics is reported to be <1% (6,7). In a prospective phase II chemoprevention trial, the compliance was very high, and 114 out of 119 patients returned for the second RPFNA (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The RPFNA procedure is well tolerated among women participating in breast cancer prevention trials, and the risk of infections requiring oral antibiotics is reported to be <1% (6,7). In a prospective phase II chemoprevention trial, the compliance was very high, and 114 out of 119 patients returned for the second RPFNA (23).…”
Section: Discussionmentioning
confidence: 99%
“…Subjects with a previous history of breast cancer underwent the procedure in their intact opposite breast. The RPFNA procedure was done as previously described (6,7). In all women, four RPFNA passes were done two each at the 3 o'clock and 9 o'clock positions in each breast.…”
Section: Methodsmentioning
confidence: 99%
“…Its action is mediated by intracellular receptors, which, with the binding of ligands, are translocated to the nucleus, where it activates gene transcription. There are two subtypes of estrogen receptors (ERα and ERβ); they exhibit distinct cell and tissue differentiation distributions (Sneige et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…C-myc gene, located on chromosome 8, is still not established as a potential prognostic marker. However, polysomy of chromosome 8 occurs frequently in breast carcinoma, and its high copy number is associated with high malignancy grade (Bofin et al 2003;Sneige et al 2006) and could be used as prognostic parameter indicating shorter survival (Tagawa et al 2003). Determination of numerical aberration of chromosome 20 in breast cancer showed that polysomy of chromosome 20 was the most prevalent aberration (90%) and that patients with a highest level of polysomy showed the worst survival (Nakopoulou et al 2002).…”
Section: Clinical Practice Experiencementioning
confidence: 99%